Seamless semantic service provisioning mechanism for ambient assisted living - Wan Musa, Wan Mohd Nur Muzaaliff (2013)
Parallel with the evolution of current technology and usage trends in Ambient Assisted Living (AAL); variety of new services are being introduced to assist dependent people to live independently, particularly elderly and people with mild dementia. Assistive services help them to carry out Activities of Daily Living (ADL) smoothly. Users are seamlessly delivered with relevant services as they roam into a new and sometimes unknown domain. To achieve this, a service discovery and provisioning mechanism beyond the current capabilities of any service platforms is required. This thesis proposes a mechanism for seamless semantic service provisioning using semantic web that is able to manage user and device mobility through semantic reasoning. The ultimate goal is to seamlessly provide users with relevant services at a specific location and time with a set of dynamic context.